Филхелен и Сојузот: Александар I, Атина и првите искри на Северот - Саракински, Војислав (Институт за национална историја, Скопје, 2016)
Simultaneously with the siege of Thasos, ten thousand Athenian and allied colonists went on their way to establish a settlement at Ennea Hodoi, a crossing controlled by the Edonians. This attempt came to a grievous end, as – their alleged hostility notwithstanding – the Edonians and Alexander the Philhellene most probably had common interests in the area. It would be very reasonable, in 479 BC, to keep an active military force and try to implement some sort of administrative overview over Edonia; fifteen years later, however, after all immediate external threats became a thing of the past, Alexander withdrew the formal border of the kingdom to the west in order to alleviate the cost of keeping soldiers and administrators that far from the capital at Aegae. This, however, did not mean that Edonia left the Macedonian sphere of interest and/or influence. Ruled by a local basileus, they obviously remained ξύμμαχοι καὶ ὑπήκοοι (“allies and subjects”), following the pattern of certain tribes in western Upper Macedonia. Accordingly, in fighting the colonists sent by Athens, they seem to have acted in cooperation with the Argeadai – a fact that took the Athenians by surprise.
The Philhellene and the League: Alexander I, Athens and the first sparks in the North